Profiling computer energy consumption on organizations - Lopes, Rui Pedro (2011)
Modern organizations depend on computers to work. Text processing, CAD, CAM, simulation, statistical analysis and so on are fundamental for maintaining high degree of productivity and competitiveness. Computers in an organization, consume a considerable percentage of the overall energy and, although a typical computer provides power saving technologies, such as suspending or hibernating components, this feature can be disabled. Moreover, the user can opt for never turning off the workstation. Well defined power saving policies, with appropriate automatic mechanisms to apply them, can provide significant power savings with consequent reduction of the power expense. With several computers in an organization, it is necessary to build the profile of the energy consumption. We propose installing a software probe in each computer to instrument the power comsumption, either diretly, by using a power meter, or indirectly, by measuring the processor performance counters. This distributed architecture, with software probes in every computer and a centralized server for persistence and decision making tries to save energy, by defining and applying organization level power saving policies.